1992
DOI: 10.1016/0163-7258(92)90009-o
|View full text |Cite
|
Sign up to set email alerts
|

Venomous mammals

Abstract: It is not widely appreciated that mammals can be venomous in the manner of snakes and lizards. However, it was first demonstrated scientifically 50 years ago in the case of the American short-tailed shrew. Subsequently, similar evidence has been obtained from European shrews and the Haitian solenodon, but research in this area has been almost completely neglected for the last 20 years. In complete contrast to what has been learned about other animal venoms, the identity and mode of action of mammal venom toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
100
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 20 publications
5
100
2
Order By: Relevance
“…Products from precipitation of the crude extracts with ammonium sulfate (33-80% saturation) are toxic. Therefore, it has been suggested that the most toxic ingredient is a high molecular weight water-soluble protein, not a carbohydrate or nucleoprotein (1). However, because the Blarina venom loses its toxicity rapidly after the victim's death, its purification and more precise identification have not been successfully completed.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Products from precipitation of the crude extracts with ammonium sulfate (33-80% saturation) are toxic. Therefore, it has been suggested that the most toxic ingredient is a high molecular weight water-soluble protein, not a carbohydrate or nucleoprotein (1). However, because the Blarina venom loses its toxicity rapidly after the victim's death, its purification and more precise identification have not been successfully completed.…”
mentioning
confidence: 99%
“…In general, soricine shrews consume large amounts of food to meet their high metabolic demands (11). Although they belong to the order Insectivora, B. brevicauda do not eat insects and invertebrates exclusively but also vertebrates, even larger than themselves, such as murid rodents and frogs (1,(11)(12)(13). Therefore, this shrew species may use its venom to paralyze and catch larger preys.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The teeth of helodermatid lizards are deeply grooved in a manner convergent with those of some advanced snakes, in which grooved, venom-delivering teeth have independently evolved on multiple occasions and display extensive variation (Russel and Bogert, 1981;, This is also convergent with various other extant and extinct venomous lineages including archosauriforms (Mitchell et al, 2010), conodonts (Szaniawski, 2009), sphenodons (Reyonso, 2005, insectivorous mammals such as shrews and solenodons (Cuenca-Bescos and Rofes, 2007;Dufton, 1992;Ligabue-Braun et al, 2012;Rofes and Cuenca-Bescos, 2009) and bird-like dinosaurs hypothesised to specialise in preying upon early birds (Gong et al, 2010).…”
Section: Anguimorphamentioning
confidence: 99%